Kant's aesthetic epistemology : form and world - Hughes, Fiona (Edinburgh University Press, 2007)
Drawing on resources from both the Analytical and Continental traditions, Form and World argues that a comprehension of Kant's aesthetics is necessary for grasping the scope and force of his epistemology. Fiona Hughes draws on phenomenological and aesthetic resources to bring out the continuing relevance of Kant's project. One of the difficulties faced in reading the Critique of Pure Reason is finding a way of reading the text as one continuous discussion. This book offers a reading at each stage of Kant's epistemological argument, showing how various elements of Kant's argument, often thought of as extraneous or indefensible, can be integrated. This incisive study, arguing for the centrality of aesthetics in philosophy, and within experience in general, challenges a blind spot in the Anglo-American tradition of philosophy and will contribute to a growing interest in the general significance of aesthetic culture.
Keywords: Kant, Immanuel, -- 1724-1804 -- Aesthetics.; Kant, Immanuel, -- 1724-1804. -- Kritik der Urteilskraft.; Kant, Immanuel, -- 1724-1804; Kritik der Urteilskraft (Kant, Immanuel); Kant, Immanuel.; Knowledge, Theory of.; Théorie de la connaissance.; epistemology.; PHILOSOPHY -- Aesthetics.; PHILOSOPHY -- Epistemology.; Aesthetics; Knowledge, Theory of; Erkenntnistheorie; Ästhetik; Electronic books.; History